Visual evaluation in the child: from the neonatal unity to the domicile - Maria Vera Lúcia Moreira Leitão Cardoso; Grazielle Roberta Freitas da Silva (Rev Rene)
This study was held in a maternity located in Fortaleza-CE, from January to May/2003. One aimed at investigating ocular disorders in children with the risk of developing visual disorders; performing visual stimulation in children taken into the neonatal unit and the kangaroo nursery in a risky state; and accompanying children who show disordered visual response. The sample was composed of 21 babies, out of critical health condition, who were taken into neonatal units. One held 86 sessions of visual stimulation, external ocular exam and evaluation of the visual activity, focusing on the basic visual responses in all the children. The commonest disorder was the nistagmo. There was domiciliary visit to the ones with disordered visual answers. Through the evaluation and visual stimulation in children taken into hospital, one can detect ocular disorders that, once identified, should be treated by specialists in time to avoid blindness in childhood.